Growing populations, changing landscapes : studies from India, China, and the United States (National Academy Press, 2001)
Uses case studies to look at population growth and land-use change through time and space. This comes from a joint project between the US Chinese and Indian Academies of Science. The NAP notes that "the Open Book page image presentation framework is not designed to replace printed books, nor emulate HTML. Rather, it is a free, browsable, nonproprietary, fully and deeply search able version of the publication which we can inexpensively and quickly produce to make the material available worldwide." Files can be printed from the OpenBook page's tool block or the linked PDF version